2007
DOI: 10.1002/ange.200702006
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of “Turn‐On” Allosteric DNAzyme Catalytic Beacons for Aqueous Mercury Ions with Ultrahigh Sensitivity and Selectivity

Abstract: Quecksilbernachweis: Ein DNAzym mit mehreren Thyminresten nahe dem katalytischen Zentrum ist inaktiv, doch Thymin‐Hg2+‐Thymin‐Wechselwirkungen überführen es in ein aktives Enzym. Durch Anbinden eines Fluorophor‐Fluoreszenzlöscher‐Paars kann das DNAzym in einen hoch empfindlichen und selektiven Quecksilbersensor mit einer Nachweisgrenze von 2.4 nM und einem Selektivitätsverhältnis über 100 000 gegenüber anderen Metallionen überführt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(75 citation statements)
references
References 55 publications
3
72
0
Order By: Relevance
“…[22,36] Furthermore, the thymidine-Hg 2+ -thymidine coordination chemistry prompted Liu, Lu, and co-workers to engineer a UO 2 2+ -dependent DNAzyme [15] into a very sensitive and selective allosteric DNAzyme that can detect mercuric cations. [37] They rationalized that because the exact composition of the stem loop had no dramatic effect on the catalytic efficiency of the DNAzyme, the appendage of up to six thymine-thymine mismatches would provide an ideal binding place for Hg 2+ . Indeed, the generated DNAzyme E Hg 5T had a rate constant of 0.61 min À1 in the presence of 10 mm Hg 2+ , displayed a high selectivity for mercuric cations, and showed a detection limit as low as 2.4 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[22,36] Furthermore, the thymidine-Hg 2+ -thymidine coordination chemistry prompted Liu, Lu, and co-workers to engineer a UO 2 2+ -dependent DNAzyme [15] into a very sensitive and selective allosteric DNAzyme that can detect mercuric cations. [37] They rationalized that because the exact composition of the stem loop had no dramatic effect on the catalytic efficiency of the DNAzyme, the appendage of up to six thymine-thymine mismatches would provide an ideal binding place for Hg 2+ . Indeed, the generated DNAzyme E Hg 5T had a rate constant of 0.61 min À1 in the presence of 10 mm Hg 2+ , displayed a high selectivity for mercuric cations, and showed a detection limit as low as 2.4 nm.…”
mentioning
confidence: 99%
“…Indeed, the generated DNAzyme E Hg 5T had a rate constant of 0.61 min À1 in the presence of 10 mm Hg 2+ , displayed a high selectivity for mercuric cations, and showed a detection limit as low as 2.4 nm. [37] Nevertheless, this system required the use of the uranyl ion (UO 2 2+ ) for activity. [15,38] Finally, the in vitro selection of RNA-cleaving DNAzymes requiring mercuric ions for catalysis has recently been reported.…”
mentioning
confidence: 99%
“…[2] Therefore, it is highly desirable to develop a sensitive and selective mercury detection method that can provide simple, practical, and high-throughput routine determination of levels of Hg 2+ ions for both environmental and food samples. Much effort has been devoted towards the design of sensing systems for Hg 2+ ions, including sensors based on organic chromophores [3] or fluorophores, [4] conjugated polymers, [5] DNAzymes, [6] gold nanoparticles, [7] semiconductor quantum dots, [8] proteins, [9] and genetically engineered bacteria. [10] However, most of these methods have some limitations such as poor selectivity with interference from closely related metals, insufficient sensitivity (limit of detection (LOD) > 100 nm), and in certain cases are nonstable or nonfunctional in aqueous media (because of low water solubility).…”
Section: Bang-ce Ye* and Bin-cheng Yinmentioning
confidence: 99%
“…[51] A highly selective oligodeoxyribonucleotide Hg 2+ sensor could be created based on this specific interaction. [52,53] Recent studies showed that also an RNA duplex synthesized by in vitro transcription can incorporate Hg 2+ ions to form uracil-Hg 2+ -uracil base pairs. [12] In vitro transcription thereby has the advantage that large amounts of nucleic acid (RNA) can be made easily.…”
Section: Artificial Metal Ions-nucleic Acids Systemsmentioning
confidence: 99%